Developing an Innovative and Creative Hands-on Lean Six Sigma Manufacturing Experiments for Engineering Education - Elbadawi, I.; Aichouni, M.; Messaoudene, N. A. (Engineering, Technology & Applied Science Research, 2016)
The goal of this study was to develop an innovative and creative hands-on project based on Lean Six Sigma experiments for engineering education at the College of Engineering at the University of Hail. The exercises were designed using junction box assembly to meet the following learning outcomes: 1-to provide students with solid experience on waste elimination and variation reduction and 2-to engage students in exercises related to assembly line mass production and motion study. To achieve these objectives, students were introduced to the principles of Lean manufacturing and Six Sigma through various pedagogical activities such as classroom instruction, laboratory experiments, hands-on exercises, and interactive group work. In addition, Minitab 17 statistical package and Quality Companion 3 software were used to facilitate The Lean Six Sigma exercises. The software application and hands-on manufacturing assembly were found to be extremely valuable in giving students the chance to identify which variables to control in order to minimize variation and eliminate waste. This research was funded by a grant from the Deanship of Academic Research at University of Hail for project number E-26-IC, and under the umbrella of Ministry of Education within the framework of the National Initiative on Creativity and Innovation in Saudi Universities at University of Hail.